2016
DOI: 10.1093/eurpub/ckw057
|View full text |Cite
|
Sign up to set email alerts
|

Child welfare clients have higher risks for teenage childbirths: which are the major confounders?

Abstract: Background: Aiming to support effective social intervention strategies targeting high-risk groups for teenage motherhood, this study examined to what extent the elevated crude risks of teenage childbirth among child welfare groups were attributable to the uneven distribution of adverse individual and family background factors. Methods: Comprehensive longitudinal register data for more than 700 000 Swedish females born 1973–1989 (including around 29 000 child welfare clients) were analysed by means of binary lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… Currie and Widom (2010) , for example, speculate that poor midlife economic outcomes in maltreated children may partially be explained by poor educational attainment. Several Swedish national cohort studies indicate that poor school and educational performance are the by far strongest predictors of OHC alumni’s social, economic, and health-related outcomes in adulthood (e.g., Brännström, Vinnerljung, & Hjern, 2016 ; Vinnerljung et al, 2015 ). Since OHC children in care tend to substantially underperform in the educational system compared to peers with similar cognitive capacity, investing in school/educational support while they are in societal care is a credible strategy ( Forsman & Vinnerljung, 2012 ; Vinnerljung et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“… Currie and Widom (2010) , for example, speculate that poor midlife economic outcomes in maltreated children may partially be explained by poor educational attainment. Several Swedish national cohort studies indicate that poor school and educational performance are the by far strongest predictors of OHC alumni’s social, economic, and health-related outcomes in adulthood (e.g., Brännström, Vinnerljung, & Hjern, 2016 ; Vinnerljung et al, 2015 ). Since OHC children in care tend to substantially underperform in the educational system compared to peers with similar cognitive capacity, investing in school/educational support while they are in societal care is a credible strategy ( Forsman & Vinnerljung, 2012 ; Vinnerljung et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This categorisation of children with OHC experience has been used in a host of previous national cohort studies (e.g. Brännström, Vinnerljung, & Hjern, ; Vinnerljung & Hjern, ), and has shown good discriminatory qualities: Short OHC ( N = 16,094): Persons who were placed in OHC for the first time before age 13 and who stayed in care less than five years totally before age 20. The average age of first placement was 6 years and the average time spent in care was 1.3 years. Long OHC ( N = 11,153 ) : Persons who were placed in OHC for the first time before age 13 and who remained in care for five years or more.…”
Section: Methodsmentioning
confidence: 99%
“…Participants only minimally discussed care leavers who did not have children (many participants only worked with parents), but some commented that young people with normative family experiences of stable relationships and placements were not tending to have children and instead finished school and progressed to university and work. Brannstrom et al (2016) similarly identified a clear relationship between girls' school failure and early parenting in a whole population study of child welfare clients. Ohene and Garcia (2020) found that educational attainment was linked with connectedness to carers and residential care staff and a positive sense of self.…”
Section: Discussionmentioning
confidence: 91%